Complete genome for Actinobacillus pleuropneumoniae serovar 8 reference strain 405: comparative analysis with draft genomes for different laboratory stock cultures indicates little genetic variation. Issue 11 (24th November 2021) - Bossé, Janine T.; Li, Yanwen; Cohen, Liza Miriam; Stegger, Marc; Angen, Øystein; Lacouture, Sonia; Gottschalk, Marcelo; Lei, Liancheng; Koene, Miriam; Kuhnert, Peter; Bandara, Aloka B.; Inzana, Thomas J.; et al.
Abstract : We report here the complete genome sequence of the widely studied Actinobacillus pleuropneumoniae serovar 8 reference strain 405, generated using the Pacific Biosciences (PacBio) RS II platform. Furthermore, we compared draft sequences generated by Illumina sequencing of six stocks of this strain, including the same original stock used to generate the PacBio sequence, held in different countries and found little genetic variation, with only three SNPs identified, all within the degS gene. However, sequences of two small plasmids, pARD3079 and p405tetH, detected by Illumina sequencing of the draft genomes were not identified in the PacBio sequence of the reference strain.